Surface Engineering of Thrombus‐Targeting Nanocarriers for Cardiovascular Diseases: A Short Review - Xinyue Ge; Lei Ding; Wenjun Zhao; Bohan Cui; Xiang Guan; Mingfei Pan; Qingguo Li; Ning Gu (Advanced Materials Interfaces)
Abstract Cardiovascular diseases (CVDs), such as ischemic heart disease and stroke—both driven by thrombotic events—are the predominant cause of global mortality. Conventional treatments, including systemic thrombolysis and mechanical thrombectomy, face challenges such as bleeding risks and complicated interventional procedures. With the advancements of pharmaceutical nanocarriers, thrombus‐targeted drug delivery strategies have emerged as a promising approach. These nanocarriers enable precise encapsulation and controlled release of therapeutic agents to enhance thrombolysis efficiency and mitigate local inflammation. This review summarizes the cutting‐edge surface modification strategies for nanocarriers, based on ligand‐receptor interactions and antibody conjugation targeting the key thrombus‐associated receptors. Furthermore, intelligent nanocarrier systems with thrombus microenvironment‐responsive (e.g., pH and thrombin concentration) and external stimuli‐responsive designs are highlighted to achieve spatially and temporally controlled drug release. Beyond thrombolysis, the role of nanocarriers in modulating inflammation, an underappreciated contributor to thrombotic pathogenesis, is discussed, emphasizing the therapeutic potential of thrombolytic and anti‐inflammatory combined therapy. It is hoped that the insights provided in this review will be a valuable reference for developing nanocarriers with biosafety and precise functions as next‐generation therapies for CVDs.